Formação de professores das séries iniciais: o pedagogo em questão - Leite, Aline Fernanda Ventura Sávio [UNESP] (2015)
This research aimed to show the importance of teacher for the learning process in the early years of elementary shool proposing a teaching science based on a constructivist reading. This paper will discuss a brief history of the Faculty of Education, the importance of continuing education for the effective teaching of natural sciences as well as their content and methodologies. We seek also explain about the history of natural science education pointing to existing legislation that supports this disciplines and Piaget's ideas on education. This research involves three objects of study through a qualitative approach to records and interviews proposed by Ludke; André; (1986) First we analyze and interview with acting teachers in a Municipal School of Interior of. Then we study the initial training of teachers through documents that make up the course as: curriculum, the menu of disciplines, political and pedagogical project, the internet pages of presentation, educational programs and projects. We will also consider the natural science content taught from first to fifth year of elementary school for an education system. In is expected that the data pointed to this research contribute to science education, for training and teacher's identify construction as well as assist in their continuing education